Industry Payment Trends to Orthopaedic Surgeons From 2014 to 2018: An Analysis of the First 5 Years of the Open Payments Database. Issue 2 (15th January 2022) - Heckmann, Nathanael D.; Mayfield, Cory K.; Chung, Brian C.; Christ, Alexander B.; Lieberman, Jay R.
Abstract : Introduction: The Open Payments Database (OPD) provides transparent reporting of all payments made to physicians from private industry. Previous studies have described the nature of these financial relationships using the first year of publicly available data. However, long-term trends of these relationships have not been well described. Therefore, we report on the value and distribution of payments within the OPD and analyze trends of payments made to orthopaedic surgeons from 2014 to 2018. Methods: The OPD was queried from 2014 to 2018. Payments within the database were categorized into (1) general payments, (2) research interests, and (3) ownership interests. We report on the number, value, and payment trends between private industry and all licensed orthopaedic surgeons who have completed residency training. Results: A total of 631, 000 physicians and 23, 859 orthopaedic surgeons were included, representing 79.8% of US board-certified orthopaedic surgeons (n = 29, 908). Although orthopaedic surgeons received an average of 2.9% of the number of payments made annually, payments to orthopaedic surgeons represented 10.0% of the value of payments made to all physicians. From 2014 to 2018, payments to orthopaedic surgeons increased in both number and value, from 313, 194 separate payments (883.8 million) in 2014 to 335, 815 separate payments (958.6 million) in 2018. In 2018, the top 1% of orthopaedic surgeons (n = 239) accounted for 58.0% (265.8 million) of all payments to the field. Despite representing only 2.4% of the number of general payments, royalties represented 68.9% (290.4 million) of the value of general payments to orthopaedic surgeons. Payments for research and education both increased. Discussion: Industry payments to orthopaedic surgeons represent 10.0% of all physician payments, with increases in payments for research and education. Royalties represented most (68.9%) of the value of general payments made to orthopaedic surgeons. Transparency in physician payments from industry is essential to avoid conflicts of interest. Level of Evidence: Level III